Advanced microstructural characterization of the intergranular oxidation of Alloy 600. (November 2015) - Bertali, G.; Scenini, F.; Burke, M.G.
Highlights: Alloy 600 is susceptible to intergranular oxidation in hydrogenated steam at 480 °C. It is demonstrated that GB migration occurs during intergranular oxidation. GB migration plays a fundamental role in Alloy 600 oxidation. GB migration is associated with localised Cr and Fe-depleted region. Abstract: Oxidation of solution-annealed Alloy 600 has been performed in a hydrogenated steam environment, which is considered to simulate PWR primary water exposure. FIB and analytical TEM characterization, coupled with detailed SEM analyses, provided unequivocal evidence of localized grain boundary migration and intergranular oxide penetrations. These localized migrations were associated with pronounced Cr and Fe depletions, highlighting the role of the grain boundaries for Cr diffusion for intergranular oxidation. These findings are discussed in relation to the early stages of intergranular oxidation, diffusion-induced grain boundary migration and subsequent SCC initiation.